2014
DOI: 10.15252/emmm.201404797
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TNF‐α mRNA stability by human antigen R and miR181s in sepsis‐induced immunoparalysis

Abstract: Immunoparalysis is an important pathological mechanism in sepsis. However, an effective small molecule therapy is lacking. Here, we show that ouabain, a Na+,K+-ATPase ligand, can reverse immunoparalysis in vitro, in vivo, and in clinical samples. Notably, the effect of ouabain was critically dependent on TNF-α expression. However, ouabain had opposing effects on the stability of TNF-α mRNA: Ouabain triggered miR-181 transcription, which promoted TNF-α mRNA degradation and induced immunoparalysis, and ouabain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 46 publications
(61 reference statements)
2
61
0
1
Order By: Relevance
“…Exposure of cell lines and animal models to LPS is a popular method for investigating their roles in inflammation. In an LPS model of murine sepsis, an increased expression of miR-15a/16 reduced the phagocytic activity of macrophages and increased mitochondrial oxidative stress, resulting in a proinflammatory phenotype [59, 60]. Overexpression of miR-15a/16 in the LPS-treated murine macrophage RAW264.7 downregulated the expression of Toll-like receptor (TLR)4 and IL-1 receptor-associated kinase 1 (IRAK1), contributing to immunosuppressive phenotypes [53, 61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of cell lines and animal models to LPS is a popular method for investigating their roles in inflammation. In an LPS model of murine sepsis, an increased expression of miR-15a/16 reduced the phagocytic activity of macrophages and increased mitochondrial oxidative stress, resulting in a proinflammatory phenotype [59, 60]. Overexpression of miR-15a/16 in the LPS-treated murine macrophage RAW264.7 downregulated the expression of Toll-like receptor (TLR)4 and IL-1 receptor-associated kinase 1 (IRAK1), contributing to immunosuppressive phenotypes [53, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR-181 enhances TNF-α mRNA degradation [60]. In a THP-1 human promonocytic cell model, miR-146a increased in a time-dependent manner on LPS/TLR4 stimulation, suppressing the production of proinflammatory cytokines in a feed-forward loop [63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…When miR-181 is deficient in a specific tissue in mice, conventional T cell and natural killer T cell development were perturbed and PI3K signaling was impaired, which results from the cumulative effect of increased PTEN expression (Henao-Mejia et al, 2013). Dan et al suggested that miR-181 upregulation is the primary host protective method against endotoxin shock, as it can switch the immune status from hyperinflammation to endotoxin tolerance by quickly decreasing inflammatory cytokine expression without influencing the expression of anti-inflammatory cytokines (Dan et al, 2014). In an experimental neuroinflammatory model, miR-181 was found to be necessary for the reactive phenotype of astrocytes to inflammatory settings by reprogramming the transcriptional profiles of general cell differentiation and stress responses (Hutchison et al, 2013).…”
Section: Mir-181mentioning
confidence: 99%
“…Previous studies have found several miRNAs targeting TNF-α in other diseases, such as miR181s, miR181c, miR-19a, miR-155, miR-125b, and miR-130a [40][41][42][43][44][45]. Several miRNAs targeting IL-8 have also been identified in non-gout diseases, such as miR-106b, miR520b, miR-203 and miR-93 [46][47][48][49].…”
Section: Mirnas and Inflammatory Cytokinesmentioning
confidence: 99%